Synergistic effect of heat shock protein 90 inhibitor, 17-allylamino-17-demethoxygeldanamycin and X-rays, but not carbon-ion beams, on lethality in human oral squamous cell carcinoma cells - Musha, Atsushi (Oxford University Press, 2012)
The purpose of this study is to clarify the effect of a heat shock protein 90 inhibitor, 17-allylamino-17-demethoxygeldanamycin (17-AAG), in combination with X-rays or carbon-ion beams on cell killing in human oral squamous cell carcinoma LMF4 cells. Cell survival was measured by colony formation assay. Cell-cycle distribution was analyzed by flow cytometry. Expression of DNA repair-related proteins was investigated by western blotting. The results showed 17-AAG to have synergistic effects on cell lethality with X-rays, but not with carbon-ion beams. The 17-AAG decreased G(2)/M arrest induced by X-rays, but not by carbon-ion beams. Both X-ray and carbon-ion irradiation up-regulated expression of non-homologous end-joining-associated proteins, Ku70 and Ku80, but 17-AAG inhibited only X-ray-induced up-regulation of these proteins. These results show that 17-AAG with X-rays releases G(2)/M phase arrest; cells carrying misrepaired DNA damage then move on to the G(1) phase. We demonstrate, for the first time, that the radiosensitization effect of 17-AAG is not seen with carbon-ion beams because 17-AAG does not affect these changes.